Amanda Thomas: capstone - Thomas, Amanda, artist (Colorado State University. Libraries, 2015)
The artist's statement: My artwork is an attempt to find spiritual order in an ever chaotic and imperfect world. My work tends to focus on control and stability, however in more recent works I have learned to embrace the results of automatic and both unconscious and conscious drawing decisions. My body of work assimilates control and chance, and some pieces reflect both simultaneously. I create works focusing on organic animal forms, utilizing them as a vessel for my emotions and thought-processes, as well as placing spiritual emphasis on them. Humans often connect to animals in certain ways, reading particular emotions for different species, therefore creating spiritual outlets through those animals; I utilize this to my advantage in my works, forcing emotions out of them that could only be done by depicting certain animals. Concurrently, my work explores the relationships that humans have with not only the animals that I depict, but with other human beings. The void of emotion that has become ever present in human interactions intrigue me, particularly my own lack of emotion towards others. I am interested in sharing imagery that I feel strongly connected to in order to record viewer reactions, so that I can experience the full range of emotional connection and witness it in others. Through these drawings, I feel closer to my audience and I hope that they feel close to me.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing; printmaking